Linkage analysis of a rare alkaloid present in a tetraploid potato with Solanum chacoense background - Sagredo, B.; Lorenzen, J.H.; Casper, H.; Lafta, A. (Springer, 2011)
The potato genotype ND4382-19 has Solanum chacoense Bitt. in its genetic background. Foliar alkaloid analysis of it and its progeny ND5873 (ND4382-19 × Chipeta) by gas chromatography–mass spectrometry (GC–MS) showed that, in addition to the expected alkaloids (solanidine, leptinidine, and acetyl-leptinidine), there was an aglycone of another rare alkaloid. Its molecular mass and some of the m/z fragment ions were similar to leptinidine, but the major fragment ion was the m/z 150 peak of solanidine. This fragmentation pattern suggested that this alkaloid is a solanidine-based compound with mass equal to leptinidine. Leptinidine differs from solanidine by an extra –OH group, but the GC–MS fragmentation pattern of the rare compound indicated hydroxylation at a different position than the C-23 of leptinidine. The exact chemical structure is still unknown, and further analysis, such as NMR will be necessary to determine the structure. Segregation analysis of ND5873 (ND4382-19 × Chipeta) showed that presence of this rare compound segregated in a 1:1 ratio, indicating that a single gene controlled its synthesis and/or accumulation in foliar tissue. Analysis with AFLP and microsatellite markers indicated that the locus-controlling presence of this alkaloid resided on potato chromosome I, with the nearest flanking AFLP markers 0.6 and 9.4 cM apart. This rare alkaloid was present in the foliage and not detected in potato tubers. Its presence in leaves did not affect resistance/susceptibility to Colorado potato beetle.